Label free-based proteomic analysis of the food spoiler Pseudomonas fluorescens response to lactobionic acid by SWATH-MS. (May 2021) - Kang, Shimo; Shi, Chunlei; Chang, Jiang; Kong, Fanhua; Li, Mohan; Guan, Boyuan; Zhang, Zhenghan; Shi, Xinyang; Zhao, Huiwen; Peng, Yanqi; Zheng, Yan; Yue, Xiqing
Abstract: Lactobionic acid (LBA) is a versatile organic acid with broad-spectrum antibacterial activity, especially against the food spoiler Pseudomonas fluorescens . However, at the proteome level, the underlying antibacterial mechanism of LBA against P. fluorescens and the P. fluorescens response to LBA are not clearly understood. In this study, a comparative proteomic analysis of P. fluorescens that responded to lactobionic acid (LBA) was performed to analyze 127 differentially expressed proteins under LBA stress, using sequential window acquisition of all theoretical mass spectra technology. Ultrastructure, reactive oxygen species (ROS), outer membrane (OM) permeability, DNA repair and ribosome self-assembly related genes expression were measured to validate the proteomic analysis. Relative quantification of targeted proteins and genes was verified using parallel reaction monitoring and real-time PCR. The integrated analysis suggested that LBA elicited oxidative stress and DNA lesions, acted as a cell wall stress signal and accelerated cell division, caused hypoosmotic shock and increased OM permeability, blocked flagellar assembly and biofilm production, increased energy generation, and inhibited nucleotide metabolism as well as protein and DNA synthesis. Therefore, our results provide a theoretical basis for application of LBA as a novel bacteriostat in the food and pharmaceutical industries. Graphical abstract: Image 1 Highlights: 127 bacterial proteins were alerted in response to Lactobionic acid by SWATH analysis. Some physiological changes of P. fluorescens were induced by Lactobionic acid. Lactobionic acid against P. fluorescens by multiple action modes. Quantification of targeted proteins and genes were verified using PRM and qRT-PCR.